2018
DOI: 10.1515/ract-2018-2961
|View full text |Cite
|
Sign up to set email alerts
|

Fast burn-up measurement in simulated nuclear fuel using ICP-MS

Abstract: A double focusing ICP-MS with pulsed laser deposition (PLD) of thin films as sampling tool has been used in simulated spent fuels for a quick measurement on burn-up of nuclear reactor fuels by measuring the atom ratio of U (representing total heavy elements of mass >225) to selected lanthanide fission monitors. A linear correlation is established between the measured intensity ratios of 238U/143Nd, 238U/(145Nd+146Nd) and 238U/139La against the actual atom ratios present in the samples. The samples in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Quantities of these elements present in the above pellets correspond to six different compositions, varying from 0.7 to 15.4 at% burn-up of FBR fuel. 24 The detailed procedure for sample preparation is given elsewhere. 31 Accurately weighed amounts of UO 2 and Nd 2 O 3 were taken as the 1 st set of samples [ESI Table 1†]; UO 2 , Nd 2 O 3 , ZrOCl 2 ·8H 2 O, CsCl and SrCO 3 were taken as the 2 nd set of samples [ESI Table 2†].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Quantities of these elements present in the above pellets correspond to six different compositions, varying from 0.7 to 15.4 at% burn-up of FBR fuel. 24 The detailed procedure for sample preparation is given elsewhere. 31 Accurately weighed amounts of UO 2 and Nd 2 O 3 were taken as the 1 st set of samples [ESI Table 1†]; UO 2 , Nd 2 O 3 , ZrOCl 2 ·8H 2 O, CsCl and SrCO 3 were taken as the 2 nd set of samples [ESI Table 2†].…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier studies on isotopic compositions of fast reactor fuel revealed that 238 Pu has very low abundance ($0.01%) in total Pu content. 24 Hence, 238 Pu will not affect the analysis of 238 U.…”
Section: Determination Of Burn-up Using the Isotopic Ratio Of Nd/umentioning
confidence: 99%
See 3 more Smart Citations